1988
DOI: 10.1111/j.2042-3306.1988.tb01496.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of xylazine and acepromazine on bronchomotor tone of anaesthetised ponies

Abstract: Summary The effects of xylazine (an α2‐adrenoceptor agonist) and acepromazine (an α‐adrenoceptor antagonist) on bronchomotor tone were investigated in seven anaesthetised, apnoeic ponies using a computer aided forced oscillation technique, which separates changes in bronchial calibre from changes in lung volume. Both agents produced bronchodilatation and a decrease in lung volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…The increase in airway pressure observed in this study could be attributed to either a decreased dynamic compliance o r an increased airway resistance, although differentiation between these two causes could not be made by the method of measurement used. In view of their finding that xylazine induced a reduction in expiratory reserve volume and bronchodilatation in anaesthetized ponies, WATNEY et al (1988) suggested that the xylazine-induced increase in airway pressure in sheep might have been due to decrease in lung volume. However, these results were in ponies which are much less sensitive to xylazine than ruminants (GREEN andTHURMON, 1988), andBROADSTONE et al (1992) found that xylazine had no effect on lung function in conscious healthy ponies.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in airway pressure observed in this study could be attributed to either a decreased dynamic compliance o r an increased airway resistance, although differentiation between these two causes could not be made by the method of measurement used. In view of their finding that xylazine induced a reduction in expiratory reserve volume and bronchodilatation in anaesthetized ponies, WATNEY et al (1988) suggested that the xylazine-induced increase in airway pressure in sheep might have been due to decrease in lung volume. However, these results were in ponies which are much less sensitive to xylazine than ruminants (GREEN andTHURMON, 1988), andBROADSTONE et al (1992) found that xylazine had no effect on lung function in conscious healthy ponies.…”
Section: Discussionmentioning
confidence: 99%
“…Xylazine is an ideal sedative, but it has physiologic effects on airways. [25][26][27][28] Because our ultimate objective was to determine the effect of albuterol sulfate on REE and work of breathing attributable to respiratory resistance, stability of measurements in sedated horses was an important determination. Second, we intended to assess the short-term repeatability of open-flow indirect calorimetry measurements in sedated horses.…”
mentioning
confidence: 99%
“…Ketamine acts against cholinergic bronchoconstriction in isolated human ( Gateau et al, 1989 ) and guinea pig bronchi ( Leblanc et al, 1987 ; Rock et al, 1989 ), and sensitised rats ( Zhu et al, 2007 ) and sheep ( Brown and Wagner, 1999 ) in vivo . Previous studies on the bronchial effects of xylazine are limited; however, almost all describe a bronchodilatative effect of xylazine through activation of bronchial alpha-2 receptors ( Watney et al, 1988 ). The discrepancy between the previously described bronchial effects of these two anaesthetics when used in isolation and our results with the combined administration of ketamine and xylazine indicates that the combination of the two drugs may result in increased airway reactivity.…”
Section: Discussionmentioning
confidence: 99%